Quality of life and religious-spiritual coping in palliative cancer care patients - Ticiane Dionizio de Sousa Matos; Silmara Meneguin; Maria de Lourdes da Silva Ferreira; Helio Amante Miot
ABSTRACT Objectives: to compare the quality of life and religious-spiritual coping of palliative cancer care patients with a group of healthy participants; assess whether the perceived quality of life is associated with the religious-spiritual coping strategies; identify the clinical and sociodemographic variables related to quality of life and religious-spiritual coping. Method: cross-sectional study involving 96 palliative outpatient care patient at a public hospital in the interior of the state of São Paulo and 96 healthy volunteers, using a sociodemographic questionnaire, the McGill Quality of Life Questionnaire and the Brief Religious-Spiritual Coping scale. Results: 192 participants were interviewed who presented good quality of life and high use of Religious-Spiritual Coping. Greater use of negative Religious-Spiritual Coping was found in Group A, as well as lesser physical and psychological wellbeing and quality of life. An association was observed between quality of life scores and Religious-Spiritual Coping (p<0.01) in both groups. Male sex, Catholic religion and the Brief Religious-Spiritual Coping score independently influenced the quality of life scores (p<0.01). Conclusion: both groups presented high quality of life and Religious-Spiritual Coping scores. Male participants who were active Catholics with higher Religious-Spiritual Coping scores presented a better perceived quality of life, suggesting that this coping strategy can be stimulated in palliative care patients.